1995
DOI: 10.1210/jcem.80.3.7883838
|View full text |Cite
|
Sign up to set email alerts
|

Insulin stimulates endothelin-1 secretion from human endothelial cells and modulates its circulating levels in vivo.

Abstract: Endothelin-1 (ET-1) is a potent vasoactive and mitogenic peptide produced by the vascular endothelium. In this study, we evaluated whether insulin stimulates ET-1 secretion by human endothelial cells derived from umbilical cord veins and by human permanent endothelial hybrid cells Ea.hy 926. Moreover, to provide evidence that insulin may stimulate ET-1 secretion in vivo, plasma ET-1 levels were evaluated in 7 type II diabetic normotensive males (mean age, 54.3 +/- 4.0 yr) during 2-h hyperinsulinemic euglycemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
82
2
4

Year Published

1999
1999
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(90 citation statements)
references
References 15 publications
2
82
2
4
Order By: Relevance
“…In a previous study, the potentiation of the vasopressin-induced vasoconstriction in mesenteric arteries of Sprague-Dawley rats was not inhibited by the selective endothelin type A receptor antagonists BQ123 [9]. In addition, in cultured endothelial cells insulin-stimulated production of endothelin-1 takes usually 2–6 h [28]. In our experimental protocol the insulin incubation time was much shorter (30 min).…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…In a previous study, the potentiation of the vasopressin-induced vasoconstriction in mesenteric arteries of Sprague-Dawley rats was not inhibited by the selective endothelin type A receptor antagonists BQ123 [9]. In addition, in cultured endothelial cells insulin-stimulated production of endothelin-1 takes usually 2–6 h [28]. In our experimental protocol the insulin incubation time was much shorter (30 min).…”
Section: Discussionmentioning
confidence: 82%
“…It has been suggested that insulin may stimulate endothelin-1 secretion from human endothelial cells [28]. Therefore, endothelin may be responsible for insulin-induced changes in vascular contractility [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated circulating levels of ET-1 have been reported in most [55, 56, 57, 58, 59, 60, 61]but not all [62, 63]studies of human insulin resistance. The ET-1 elevation has been reported to be proportional to the hyperinsulinemia [64, 65, 66], and a dietary weight loss can reduce both serum insulin and ET-1 concentrations [67]. Furthermore, acute endogenous and exogenous elevations in circulating insulin levels in normal controls and in insulin-resistant subjects have been shown to acutely elevate circulating ET-1 [56, 68, 69], although again dissenting findings exist [70, 71, 72].…”
Section: The Hyperinsulinemia Questionmentioning
confidence: 99%
“…On the other hand, ET-1 is known to act on adipocytes, affecting adipogenesis (57,58) and glucose metabolism (59,60). Interestingly, leptin and ET-1 production are both activated by insulin (25,61,62) and inhibited by peroxisome proliferator-activated receptor-␥ agonists (30,63), suggesting an intimate relationship among these factors.…”
Section: Endothelin-1 As An Activator Of Leptin Productionmentioning
confidence: 99%